PENGARUH PROFESIONALISME DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT BATANG CENAKU KABUPATEN INDRAGIRI HULU - Saputra, H.R. Marwan Indra (Eko dan Bisnis: Riau Economic and Business Review, 2019)
This research is at the Batang Cenaku Sub-District Office in Indragiri Hulu Regency. The purpose of this study is to determine the effect of professionalism and work discipline on employee performance at the Batang Cenaku District Head Office in Indragiri Hulu Regency, both simultaneously and partially. To collect all the data, this research used interview and questionnaire using multiple linear regression analysis methods. The sampling method using purposive sampling method with a total sample of 35 respondents. The results of this study are: Constants of -2.669 means that this constant value indicates that if there is no professionalism variable (X1) and work discipline (X2) or the value is 0, then employee performance (Y) decreases by 2,669. The regression coefficient of professionalism variable (X1) is 1.049. This means that if professionalism rises by one unit while the work discipline variable is stable, then employee performance increases by 1,049. Regression coefficient of work discipline variable (X2) is 0.324 meaning that if the variable professionalism is stable and work discipline has a one unit increase, then employee performance (Y) rises by 0.324. The Fsimultan Test Result states that the Fcount results obtained are 19,720 with a significance value of 0.002. So Fcount> Ftable (19,720> 3.29) or Sig F <5% (0.002 <0.05) Because the significance value of the F test is smaller than the significant level of 0.05, and Fcount> Ftable then Ho is rejected and Ha is accepted so it means that Simultaneously professionalism and work discipline have a significant effect on employee performance. Obtained R number equal to 0.743 means close to 1, so here it can be said that the influence of professionalism and work discipline on employee performance has a strong and positive relationship. Meanwhile, based on the analysis table above, the number R2 (R Square) is obtained or the coefficient of determination is 0.552. meaning 55.2%. shows the percentage of contribution of independent variables (professionalism and work discipline) to the dependent variable (employee performance) Or the variation of the independent variables used in the model (professionalism and work discipline) is able to explain 55.2% of the variation of the dependent variable (employee performance). While the remaining 44.8% is influenced by other variables not examined in this study